Evaluation of Electronic Health Record Data Quality: A Case Study of a Government General Hospital in Jakarta - Iindra Iriyanti; Isnina Eva Hidayati; Nur Indrawati; Dana Indra Sensuse (Eduvest - Journal of Universal Studies, 2026)
The digital transformation of healthcare is a global priority for improving service efficiency, information system integration, and data-driven decision-making. In Indonesia, government hospitals are pioneering the implementation of digital transformation policies through the SATUSEHAT program, which aligns with the Health Level Seven International (HL7) initiative to implement global health data interoperability standards. This program requires the hourly submission of Electronic Health Record (EHR) data to the Ministry of Health of the Republic of Indonesia’s SATUSEHAT platform, with the requirement that the data meet the dimensions of completeness, accuracy, timeliness, and consistency. This study aims to evaluate the quality of EHR data at a central government general hospital in Jakarta using the Total Data Quality Management (TDQM) framework and linking it to the principles of HL7 Fast Healthcare Interoperability Resources (FHIR). This study involved in-depth interviews with the EHR development team and a quantitative analysis of data from the hospital’s Health Information System (HIS) and data warehouse for outpatients during the period of December 1–31, 2025. The results showed that the quality of EHR data did not fully meet the four main dimensions of data quality. A total of 13.16% of EHR data was rejected by the SATUSEHAT platform. Key recommendations include synchronizing population data with the Directorate General of Population and Civil Registration and improving data quality governance capabilities within government hospitals. This research provides a strategic contribution to national efforts to build an integrated, interoperable, and globally standardized digital health system.